2012
DOI: 10.7150/thno.4290
|View full text |Cite
|
Sign up to set email alerts
|

The Invasion and Reproductive Toxicity of QDs-Transferrin Bioconjugates on Preantral Follicle in vitro

Abstract: The toxicity of QD has been extensively studied over the past decade. However, the potential toxicity of QDs impedes its use for clinical research. In this work, we established a preantral follicle in vitro culture system to investigate the effects of QD-Transferrin (QDs-Tf) bioconjugates on follicle development and oocyte maturation. The preantral follicles were cultured and exposed to CdTe/ZnTe QDs-Tf bioconjugates with various concentrations and the reproductive toxicity was assessed at different time point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 29 publications
2
24
1
1
Order By: Relevance
“…They reported that the nanoparticles perturbed the mitochondrial membranes of granulosa cells, and eventually affected the steroidogenesis via an oxidative stress-mediated mechanism. Our previous work also confirmed that the QDs could be uptaken by granulosa cells and theca cells in vitro 1931.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…They reported that the nanoparticles perturbed the mitochondrial membranes of granulosa cells, and eventually affected the steroidogenesis via an oxidative stress-mediated mechanism. Our previous work also confirmed that the QDs could be uptaken by granulosa cells and theca cells in vitro 1931.…”
Section: Resultssupporting
confidence: 73%
“…In the first case, the oocyte with immatured cytoplasm contained in COCs will decrease the in vitro fertilization. The oocyte maturation includes nuclear maturation and cytoplasmic maturation19. The oocyte nucleus maturation characterizes with a released first polar body.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plusieurs é tudes in vitro sur la reprotoxicité des quantum dots ont é té mené es sur des cellules folliculaires ou des ovocytes murins. En 2012, Xu et al [68], ont montré que des QDs conjugué s à la transferrine affectaient la maturation ovocytaire en s'accumulant dans les cellules de la granulosa (mais pas dans l'ovocyte), interfé raient avec le processus de maturation ovocytaire et perturbaient le signal entre les cellules germinales et les cellules somatiques gonadiques. L'é quipe de Wang [69] a é galement retrouvé une diminution du taux d'ovocytes matures dans les follicules exposé s in vitro par rapport aux contrô les non exposé s et une accumulation des QDs dans les cellules folliculaires.…”
Section: Effets Sur Les Cellules Gonadiques Fe´mininesunclassified